Phalaenopsis arunachalensis sp. nov. (Orchidaceae: Epidendroideae: Aeridinae) A new epiphytic orchid from Arunachal Pradesh, Northeast India - Gogoi, Khyanjeet; Rinya, Koj (Lankesteriana: International Journal on Orchidology, 2020)
A new epiphytic Phalaenopsis is described from tropical evergreen forests of Ziro Valley in Arunachal Pradesh, India, and illustrated with colored photos. It is allied to the similarly colored P. taenialis (Lindl.) Christenson & Pradhan in having non-deciduous leaves, larger perianth segments, the shorter and convex (not flat) lip mid-lobe, and the yellowish-green (not purplish) spur. The new species is morphologically most similar to P. honghenensis from China, but differs most easily by the light pinkish flowers versus bronzy green to brownish flowers of the latter species. A detailed description with corresponding color photos and information on the habitat is provided. The voucher specimens have been deposited at the Herbarium of the Orchid Research Centre Tippi, Arunachal Pradesh, and the Herbarium of The Orchid Society of Eastern Himalaya (TOSEHIM), Regional Orchid Germplasm Conservation and Propagation Centre (Assam Circle), Assam. Key Words: Flora of India, new Phalaenopsis, Phalaenopsis honghenensis, Phalaenopsis subgen. Aphyllae, P. taenialis